Structural health monitoring of cylindrical structures using guided ultrasonic waves - Gaul, Lothar; Sprenger, Helge; Schaal, Christoph; Bischoff, Stefan (Acta mechanica, 2012)
The research field of structural health monitoring (SHM) in the realm of civil engineering has emerged rapidly. SHM concepts are based on integrated sensors and actuators to evaluate the structural state. Beside common structural response methods and other nondestructive testing techniques, wave-based ultrasonic techniques are widely used especially because of their flexibility. Monitoring cable structures such as overhead transmission lines or stay cables in suspension bridges is one objective of those wave-based methods. These structures are subject to aging, corrosion and other static and dynamic loads (e.g., wind, temperature). The cylindrical structures act as waveguides whereby monitoring of large distances with a single ultrasonic transducer is possible. However, the wave propagation is multimodal and dispersive, which complicates analysis of the wave motion and development of monitoring applications. This work addresses several aspects of the propagation of guided waves in cylinders, especially the analysis of reflection and transmission at discontinuities using finite element and boundary element methods.